Gamified learning: merging education and entertainment - Azmi, Sharina Salmi; Halim, Nurul Syafawani; Vijayarajoo, Angeline Ranjethamoney; Adnan, Afni Anida (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The combination of entertainment and education, known as edutainment, has transformed education by making it more engaging, interactive, and enjoyable. Introducing game-like features, such as points and badges, into the learning process has made learning more captivating and pleasurable for students. Compared to traditional techniques, where students often become bored and lose interest in their studies, the combination of entertainment with education has proven highly beneficial in improving student motivation and engagement. Edutainment makes learning more enjoyable, and gamification encourages student participation and teamwork. The rise of edutainment makes traditional teaching methods less appealing because edutainment has developed a new learning style for the learning process. It offers an interactive environment, makes learning enjoyable and ultimately draws them back to the learning environment. Students are required to engage closely with the course material through activities such as Kahoot and Quizziz (Das, 2023).